First realisation of the kilogram with the METAS Kibble balance. (1st April 2022) - Eichenberger, A; Baumann, H; Mortara, A; Tommasini, D; Reber, D; Klingelé, E; Jeanneret, B; Jeckelmann, B
Abstract: After several years of development and continuous improvement, the Kibble balance at the Federal Institute of Metrology (METAS) is now operational. Its stability and reliability allows high precision measurements to be performed under vacuum. Two measurement campaigns were conducted in 2021 with 1 kg stainless steel test masses. The result differs from the value deduced from the calibration following the dissemination process after the redefinition of the kilogram by 6 μg with a total standard uncertainty of 43 μg ( k = 1). This paper presents the details of this first result with its associated uncertainty budget.